(untitled) (Geo-Eco-Marina, 2022)
Plastic particles have entered both aquatic and terrestrial ecosystem since the industrialization era, reaching dangerous levels of pollution throughout the entire food chain. The amount of microfibers quantified from several individuals of Mytilus galloprovincialis collected nearby the Constanta harbour was determined by microscopic evaluation, a high variation of the ingested particles being noted. The number of microfibers in the mussels soft tissue ranged from 0 to 14, being negatively correlated with the length and weight of the mussels. With an average concentration of 6.05 MPs per individual, fibers represent over 90% of the identified microplastics. Moreover, the microplastic concentrations reflect a high degree of pollution of the sampling area, previously observed in marine surface water and sediments.